Pessoas em situação de rua: a saída para a saída - um estudo sobre pessoas que saíram da rua - Medeiros, Alessandra (2010)
This paper provides an overview of people who have overcome homelessness. It also seeks to identify and analyze factors of both objective and subjective order - that might have effectively contributed to that outcome. The purpose of this study was, in the first place, to hear some people who have experienced the process mentioned before. By doing so, our aim was not only to comprehend their perception on what happened to them, but also to verify if nowadays social assistance policy can claim any impact on those events. Secondly, we tried to propose methodological principles - based on those perceptions and also with the support of literature that has already been produced on that theme - which might be applied on programs devised for homeless adults. This theme justifies itself by the growing number of people living in those conditions, especially in large cities ; and also because most discussions have their focus on the reasons that could lead to homelessness, ignoring the factors that might help succesfully overcome it. Thus, the following hypotheses were tested: As there are moments / events (processes) that might culminate in the homelessness phenomenon, are there moments / events / stimuli (processes) that encourage people to leave the streets? If so, can such moments be stimulated by the methodology apllied to social assistance ? In order to address those questions, two surveys were conducted: the first interwied some social workers who deal with that population; the latter is a qualitative research that brings statements from eight people who have overcome homelessness. Although not susceptible to generalization due to its nature -, this paper believes that the perceptions of those who have overcome homelessness should be regarded as a major contribution to further development of public policy